2020
DOI: 10.1142/s1005386720000267
|View full text |Cite
|
Sign up to set email alerts
|

Homological Dimensions of Skew Group Rings

Abstract: Let R be a ring and let H be a subgroup of a finite group G. We consider the weak global dimension, cotorsion dimension and weak Gorenstein global dimension of the skew group ring RσG and its coefficient ring R. Under the assumption that RσG is a separable extension over RσH, it is shown that RσG and RσH share the same homological dimensions. Several known results are then obtained as corollaries. Moreover, we investigate the relationships between the homological dimensions of RσG and the homological dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Since the left 0-perfects rings are the left perfects rings, if we take n = 0 we recover [42,Corollary 2.12]. Taking H as the trivial group we have the following corollary.…”
Section: Propositionmentioning
confidence: 74%
See 2 more Smart Citations
“…Since the left 0-perfects rings are the left perfects rings, if we take n = 0 we recover [42,Corollary 2.12]. Taking H as the trivial group we have the following corollary.…”
Section: Propositionmentioning
confidence: 74%
“…Observe that, if n = 0 we recover [42,Proposition 2.3]. Futhermore, in this case Xiang showed that the cotorsion global dimension of R is less than or equal the cotorsion global dimension of RG [42, Theorem 2.7].…”
Section: N-cotorsion Modulesmentioning
confidence: 80%
See 1 more Smart Citation
“…In recent decades, representation and homological properties of group rings have been extensively studied (cf. [1], [4], [6], [9], [14], [15], [17], [18], [19]). Among others, Connell in [6] considered necessary and sufficient conditions on R and G so that R[G] have some ring theoretic properties such as being Artinian, regular, self-injective and semiprime.…”
Section: Introductionmentioning
confidence: 99%